FEMINISM SPIRIT TOWARD PATRIARCHAL SOCIETY MANIFESTATED BY KATE REDDY IN I DON’T KNOW HOW SHE DOES IT THE MOVIE - RAMDHANI, NADIYA FARISYA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Feminism, Patriarchal Society, Working WomenWomen subordination has running for a long time ago. Women are trapped by patriarchal society’s rule on how they should be. Women never have the opportunities to get a better quality of life, such as education or career. Nowadays, women have more chance to free themselves from that social construction. The movie entitled I Don’t Know How She Does It reveals working woman’s life surrounded by patriarchal society and her effort to prove that woman can live the life she wants to.Sociological approach is used because this research relates to society and its phenomenon. The objective of the study is to observe Kate Reddy’s effort as a working woman in balancing her work-life with motherhood around patriarchal society using feminism.The result reveals that Kate Reddy can free herself from society’s construction by being a successful working woman who can balance her workinglife and motherhood.The next researcher can use phychoanalysis to find out Kate Reddy’s psychology as working woman who lives in patriarchal society.